2019
DOI: 10.1001/jamanetworkopen.2019.5844
|View full text |Cite
|
Sign up to set email alerts
|

Association of High-Intensity Binge Drinking With Lipid and Liver Function Enzyme Levels

Abstract: Key Points Question What changes in circulating lipid and liver function enzyme levels are associated with high-intensity binge drinking? Findings In this cross-sectional study of 1519 participants, high-intensity binge drinking was associated with increased cholesterol, triglyceride, and liver function enzyme levels. Meaning Lipid and liver function enzyme levels demonstrate dose-dependent increases with high-intensity binge dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 52 publications
3
27
1
1
Order By: Relevance
“…Binge alcohol consumption was significantly associated with HDL-C, after adjusting for factors of binge drinking. The present results differed from the findings of Rosoff et al [ 20 ], who reported a significant association between high-volume binge drinking and high cholesterol, triglycerides, and liver function enzyme levels. Furthermore, Klatsky and Gunderson [ 21 ] reported a significant association between binge drinking and hypertension, which was different from the findings of the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Binge alcohol consumption was significantly associated with HDL-C, after adjusting for factors of binge drinking. The present results differed from the findings of Rosoff et al [ 20 ], who reported a significant association between high-volume binge drinking and high cholesterol, triglycerides, and liver function enzyme levels. Furthermore, Klatsky and Gunderson [ 21 ] reported a significant association between binge drinking and hypertension, which was different from the findings of the current study.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings also support the causal role of alcohol consumption in increasing HDL-C as reported in previous MR studies 18,26 and provides evidence for the finding after controlling for smoking behavior. While we were unable to evaluate the effects of heavy alcohol consumption on HDL-C levels, we recently reported a cross-sectional study findings that very heavy alcohol consumption (> 10 standard drinks for men and > 8 standard drinks for women) to be associated with increased HDL-C 46 , which suggests that alcohol may impact HDL-C levels across a range of alcohol consumption levels.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, tobacco and alcohol are considered major cardiovascular risk factors. Drinking alcohol is known to raise both HDL-C and total cholesterol concentrations [30], and the concurrent use of tobacco and alcohol enhances these increases [31]. Although the mean values of HDL-and total cholesterol were not higher in SLT users (compared to nonusers), the mean values of concurrent current SLT and alcohol users increased, significantly for total cholesterol ( Table 2).…”
Section: Co-use Of Alcoholmentioning
confidence: 96%